2014
DOI: 10.5901/mjss.2014.v5n18p55
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Cities in Russia According to the Concept of "Smart City" in the Context of the Application of Information and Communication Technologies

Abstract: The article deals with the "smart city " concept, which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Screening examined citations that leave space for further exploration resulted in 48 publications as shown in Table 1 Anthopoulos (2015); Anthopoulos and Fitsilis (2013); Bakici et al (2013); Baron (2012); Batty et al (2012); Bellini et al (2014); Calvillo et al (2016); Caragliu et al (2011); da Cruz and Marques (2014); De Marco et al (2015); Desouza and Flanery (2013); Duarte et al (2014); Edvinsson (2016); Fan et al (2016);Fei. (2012); Giffinger et al (2007); Glebova et al (2014); Hancke et al (2013); Kii et al (2014); Kourtit et al (2014); Hollands (2008); ISO (2014); ITU (2014); Lazaroiu and Roscia (2012); Liu et al (2014); Lee et al (2013); Lee et al (2014); Leydesdorff and Deakin (2011); Lombardi et al (2012); Malek (2010); Marsal-Llacuna et al (2015); Mori and Christodoulou (2012); Naphade et al (2011); Neirotti et al (2014); Pires et al (2014); Shapiro (2006); Shwayri (2013); Singhal et al (2013); Söderström et al (2014); Strategic Energy Technologies Information System (SETIS) (2012);…”
Section: Research Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…Screening examined citations that leave space for further exploration resulted in 48 publications as shown in Table 1 Anthopoulos (2015); Anthopoulos and Fitsilis (2013); Bakici et al (2013); Baron (2012); Batty et al (2012); Bellini et al (2014); Calvillo et al (2016); Caragliu et al (2011); da Cruz and Marques (2014); De Marco et al (2015); Desouza and Flanery (2013); Duarte et al (2014); Edvinsson (2016); Fan et al (2016);Fei. (2012); Giffinger et al (2007); Glebova et al (2014); Hancke et al (2013); Kii et al (2014); Kourtit et al (2014); Hollands (2008); ISO (2014); ITU (2014); Lazaroiu and Roscia (2012); Liu et al (2014); Lee et al (2013); Lee et al (2014); Leydesdorff and Deakin (2011); Lombardi et al (2012); Malek (2010); Marsal-Llacuna et al (2015); Mori and Christodoulou (2012); Naphade et al (2011); Neirotti et al (2014); Pires et al (2014); Shapiro (2006); Shwayri (2013); Singhal et al (2013); Söderström et al (2014); Strategic Energy Technologies Information System (SETIS) (2012);…”
Section: Research Approachmentioning
confidence: 99%
“…In this respect, Anthopoulos (2015) compared eight (8) models and concluded to a seven-axe modeling tool, which confirms the previously mentioned 6 dimensions of smart city (Giffinger et al, 2007) and extends them with coherency in terms of social equity and engagement, while Neirotti et al (2014) extend it with the incorporation of smart building. Glebova et al (2014) conceptualize smart city with 5 key elements (intellectual transport system, public security, energy consumption management and control, environmental protection and ICT) and they define indexes to measure ICT component in Russian cities. Hollands (2008) discusses about smart city structure in terms of instrumentation (based on data collection), interconnection (enable data flow) and smart (utilize data to improve urban living).…”
Section: Findings 31 Smart City Conceptualization Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, Glebova et al [29] conceptualized the smart city with 5 dimensions: intellectual transport systems, public security, energy consumption management and control, environmental protection and ICT. Alternately, Bellini et al [30] suggested the model based on a data-oriented IT perspective: data sources, administration, street-guide, point-of-interest, local public transport, sensors, temporal, and metadata.…”
Section: Comparing Conceptual Framework On Smart Cities and Smart Tomentioning
confidence: 99%